The Impact of WhatsApp in EFL Class on Student's Learning Performance of Second-Grade Students of SMA Xaverius Ambon - Titirloloby, Piter (International Journal of Engineering, Science and Information Technology, 2023)
Technology in the 21st century is valid in human social life. Almost all people all over the world use technology to complete their needs. Using the WhatsApp application on mobile phones or social media connected with a network of students in SMA Xaverius Ambon is more beneficial. This research focuses on the actual condition related to the impact of WhatsApp in EFL classes on The learning performance of second-grade students of SMA Negeri Xaverius Ambon. The researcher used a survey design to find the results of the students in the EFL Classroom perspective in using WhatsApp on students' learning performance. Fifty students' perspective answers from class A and class B of the second grade of SMA Negeri Xaverius Ambon were interviewed, and 50 questionnaires were given to students in the classroom. This research maintained that harmful purpose impacts the student's learning performance more. This research revealed that WhatsApp can be used to communicate easier and faster, providing specific and practical information and sharing knowledge among students; instead, it is acquired negatively on the performance of SMA Xaverius Ambon students. The findings of this research can be beneficial to SMA Xaverius EFL students and classroom teachers in developing WhatsApp in the teaching and learning process.